Middle-Income Countries : Development Challenges and Growing Global Role - Fallon, Peter; Hon, Vivian; Qureshi, Zia; Ratha, Dilip (World Bank, Washington, DC, 2014)
There has been much debate recently about the role of international development institutions, such as the World Bank in middle-income countries. Some observers have suggested that middle-income countries have reached a stage in their economic development that calls into question the rationale for development institutions' continued engagement in these countries. But the authors find that middle-income countries continue to face significant development challenges. The nature of these challenges varies substantially, but all of these countries face an agenda calling for continued partnership with the international development community. Middle-income countries still have high levels of poverty. They are home to more than three-quarters of the world's poor (those living on less than U$S 2 a day). Poverty is pervasive in some middle-income countries, while in others the problem is one of major concentrations of poverty in backward areas. And recent crises have revealed the fragility of some of the gains against poverty in these countries. On the policy front, some countries have made great strides in reform, but many lag considerable behind, and even among the advanced reformers, the unfinished policy agenda is substantial. The countries' institutional capacity to manage reform varies greatly. So does their integration with the global economy. Many middle-income countries still have little access to international capital markets, and even those with better access, must contend with volatility in private capital flows. Beyond the need to assist middle-income countries in addressing these challenges, the case for continued engagement by international development institutions, derives from the increasing importance of these countries for a range of global public goods. With their growing role, and integration in the global economy, partnership with middle-income countries is a key element of global collective action, in such areas as reducing global poverty, maintaining international financial stability, improving global economic governance, protecting the global environmental commons, and fighting systemic health threats.